Heart rate reduction using ivabradine protects against periprocedural myocardial injury and angina symptoms in patients with stable coronary disease undergoing coronary intervention: Znižanje srčne frekvence z ivabradinom zmanjša periproceduralno poškodbo srčne mišice po koronarnem posegu in izboljša simptome angine pektoris pri bolnikih s stabilno koronarno boleznijo - Naji, Franjo; Berro, Marcel; Suran, David; Kanic, Vojko (Acta Medico-Biotechnica, 2021)
Purpose: There are no data demonstrating that a decrease in heart rate reduces periprocedural myocardial injury (PMI) in patients undergoing elective percutaneous coronary intervention (PCI). Ivabradine is an established anti-ischemic drug that reduces heart rate (HR) and subsequently alleviates symptoms of angina. The present study sought to determine whether HR reduction via ivabradine attenuates PMI.Methods: Forty patients with stable angina and a resting HR of >70 bpm were administered 5 mg of ivabradine twice daily. The control group consisted of 40 patients with a resting HR of >70 bpm. All patients were monitored for one month before the scheduled intervention. After admission, troponin I levels were measured before and 24 h after the procedure. Data on any change in symptoms were also collected in both groups.Results: There were no significant differences between the groups. A significant reduction in HR and angina episodes per week was noted in the ivabradine group (62.3±7.1 bpm vs.79±10.2 bpm; P
Keywords: heart rate; coronary angiography; mycardial periprocedural injury